What Happened in Bolivia's 2019 Vote Count?. Issue 6 (1st November 2020) - Long, Guillaume; Rosnick, David; Kharrazian, Cavan; Cashman, Kevin
Abstract: On October 20, 2019, Bolivia held presidential and parliamentary elections. Shortly after preliminary results indicated that incumbent president Evo Morales had won the election in the first round, the Organization of American States Electoral Observation Mission in Bolivia issued an initial postelection press release, which expressed "its deep concern and surprise at the drastic and hard-to-explain change in the trend of the preliminary results revealed after the closing of the polls, " without providing any evidence for its claims. We analyzed the claims from the Organization of American States and found: The preliminary results from the "quick count" for the first 83.85 percent of the vote count are consistent with a final projected result of Evo Morales winning the election outright with a more than 10 percentage point victory; Neither the OAS mission nor any other party has demonstrated that there were widespread or systematic irregularities in the elections of October 20, 2019; Neither the quick count nor the official count exhibit significant changes in voting trends in the final results; rather, the same well-known trend, explainable by differences in voter preferences in different geographical areas, is evident in both counts; The legally binding vote count—the official count—did not stop for any significant period of time; and It is unclear how the OAS mission's objections regarding the quick count would affect the official count.